1982
DOI: 10.1111/j.2044-8279.1982.tb02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Reading Programme: An Evaluation

Abstract: SUMMARY.The four purposes of this paper were: (a) to provide further evaluative data on the Corrective Reading programme; (b) to carry out action-research with the aim of organisational change in the host secondary school; (c) to demonstrate within-school evaluation; and ( d ) to experiment with an alternative role to that of casework for an educational psychologist.Some of the Direct Instruction and the Corrective Reading programme literature was reviewed. A model of evaluation incorporating a planned-chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…However, there is a limited research base on the effectiveness of direct instruction reading programs with children with learning disabilities. Although some studies have found very positive results (e.g., Gregory, Hackney, & Gregory, 1982; L'E. Stein & Goldman, 1980;Summerell & Brannigan, 1977), others have found limited success with the use of direct instruction reading programs such as Corrective Reading (Polloway, Epstein, Polloway, Patton, & Ball, 1986) and Distar (Kuder, 1990).…”
mentioning
confidence: 96%
“…However, there is a limited research base on the effectiveness of direct instruction reading programs with children with learning disabilities. Although some studies have found very positive results (e.g., Gregory, Hackney, & Gregory, 1982; L'E. Stein & Goldman, 1980;Summerell & Brannigan, 1977), others have found limited success with the use of direct instruction reading programs such as Corrective Reading (Polloway, Epstein, Polloway, Patton, & Ball, 1986) and Distar (Kuder, 1990).…”
mentioning
confidence: 96%
“…For adolescents, a prime exam-448 THE JOURNAL OF SPECIAL EDUCATION VOL 27/NO. 4/1994 pie is the Corrective Reading Program (Engelmann, Becker, Hanner, & Johnson, 1989) (see also Gregory, Hackney, & Gregory, 1982;Polloway, Epstein, Polloway, Patton, 8c Ball, 1986). However, although such programs can be effective with older students, they are nonfunctional if they do not result in skills that can be applied in the community.…”
Section: Content Modelsmentioning
confidence: 98%
“…However, there has been substantial support for instructional strategies in which group arrangements are an essential element. In particular, direct instruction programs have demonstrated effeaiveness for students identified as mildly handicapped, disadvantaged, and slow learners (e.g., Becker, 1977;Becker & Carnine, 1980;Gregory, Hackney, & Gregory, 1982;Stevens & Rosenshine, 1981).…”
Section: Remedial and Special Educationmentioning
confidence: 98%